2020
DOI: 10.3390/su12177040
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Investigation of Carbon-Based Adsorbent–Adsorbate Pairs for Heat Transformation Application

Abstract: In this study, the ideal adsorption cycle behavior of eight activated carbon and refrigerant pairs is evaluated. The selected pairs are KOH6-PR/ethanol, WPT-AC/ethanol, Maxsorb-III/methanol, Maxsorb-III/CO2, Maxsorb-III/n-butane, Maxsorb-III/R-134a, SAC-2/R32 and Maxsorb-III/R507a. The following cooling performance parameters are evaluated for all pairs: specific cooling energy (SCE), concentration difference (ΔW) and coefficient of performance (COP) of ideal adsorption cooling and refrigeration cycles. The ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…These directives concern, for example, the reduction of greenhouse gas emissions, supporting the development of renewable energy and low-carbon technologies, as well as the Emissions Trading System [1]. Similar efforts are also carried out at the global level, as exemplified by the Paris Agreement adopted at the Paris Climate Energies 2020, 13, 5827; doi:10.3390/en13215827 www.mdpi.com/journal/energies Energies 2020, 13, 5827 2 of 13 Conference (COP21) in December 2015 [2], and the 24th Conference of the Parties to the United Nations Framework Convention on Climate Change (COP24) at Katowice in 2018 [3]. The main aims of the agreements made during the conferences mentioned above are reducing energy and natural resources consumption and minimizing the level of pollution emitted to the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These directives concern, for example, the reduction of greenhouse gas emissions, supporting the development of renewable energy and low-carbon technologies, as well as the Emissions Trading System [1]. Similar efforts are also carried out at the global level, as exemplified by the Paris Agreement adopted at the Paris Climate Energies 2020, 13, 5827; doi:10.3390/en13215827 www.mdpi.com/journal/energies Energies 2020, 13, 5827 2 of 13 Conference (COP21) in December 2015 [2], and the 24th Conference of the Parties to the United Nations Framework Convention on Climate Change (COP24) at Katowice in 2018 [3]. The main aims of the agreements made during the conferences mentioned above are reducing energy and natural resources consumption and minimizing the level of pollution emitted to the environment.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many methods of increasing the COP have been investigated. For example, Shabir et al [13] investigated the COP of the adsorption chiller with different adsorbent/refrigerant pairs. It was found that among the investigated pairs (KOH6-PR/ethanol, WPT-AC/ethanol, Maxsorb-III/methanol, Maxsorb-III/CO 2 , Maxsorb-III/n-butane, Maxsorb-III/R-134a, SAC-2/R32, and Maxsorb-III/R507a), the Maxsorb-III/methanol pair showed the highest COP.…”
mentioning
confidence: 99%
“…For example, desiccant air-conditioning (AC) involves adsorbate and water for the dehumidification process of process air [21,22]. The central systems included are desiccant [23][24][25], adsorption [26][27][28], and absorption technologies [29][30][31][32].…”
Section: Figmentioning
confidence: 99%
“…Adsorption based AWH is a vital technology that can provide cost-effective water in arid areas. The vapor concentration in this technology can be achieved through desiccant materials which ad/absorb and desorb the water vapors from the air [45]. In this context, efficient desiccant materials are a key research priority and various materials have been developed.…”
Section: Progress and Perspectives In Adsorption Based Awhmentioning
confidence: 99%